Development and approbation of a tool for assessing municipal infrastructure affecting behavioral risk factors for cardiovascular and other noncommunicable diseases - M. V. Popovich; A. V. Kontsevaya; V. A. Zinovieva; S. V. Glukhovskaya; A. N. Savchuk; D. K. Mukaneeva; A. A. Antsiferova; Е. V. Usova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To present first results of the study on the assessment of municipal infrastructure using specialized software in a pilot subject of the Russian Federation (Sverdlovsk Oblast).Material and methods. The following infrastructure elements of four municipalities of the Sverdlovsk Oblast have been assessed in the period from January to March 2022: sports facilities, grocery stores, fairs/markets with fresh vegetables and fruits, alcoholic drinks in shops and supermarkets, special liquor stores, tobacco outlets, fast food restaurants). The assessment was made with specialized software developed using Open Street Map (OSM) that allows real-time recording of objects for interactive map data visualization.Results. The density of sales outlets for tobacco, alcohol, fresh vegetables and fruits was 2,3, 3,4 and 2,4 per 1 km², respectively; the density of sports facilities, fast food and restaurants — 1,3, 0,9 and 0,5, respectively. The number of sales outlets for tobacco, alcohol, fresh vegetables and fruits per 100 thousand people was 111,6, 167,7 and 116,5, respectively, while the number of sports facilities, fast food and restaurants — 63,5, 44,1, 25,0, respectively.Conclusion. Creation and implementation of integrated system for assessing a unified preventive environment for promoting health and maintaining a healthy lifestyle at the municipal level using a combination of objective (GIS technologies, paraclinical tests) and subjective assessment methods (personal survey), as well as the introduction of interactive maps of municipal infrastructure, will make possible use of evidence to make decisions on the development and implementation of programs for the prevention of cardiovascular diseases and health promotion, as well as their management at the regional/municipal level.